Defending Oneself in the Absence of Goodwill: Nietzschean and Spinozist Critique in Franz Kafka - D. Stevens , Zachary (Labyrinth, 2025)
This essay aims to delineate the structure shared between Kafka’s three novels, Amerika, The Trial, and The Castle, using ideas from Spinoza and Nietzsche, with whom Kafka had familiarity since his youth, namely, Spinoza’s idea that the true essence of religion is justice and charity and Nietzsche’s idea that justice is born from magnanimity, in order to grasp Kafka’s critique of certain unnecessary realities of broadly administered justice. All three novels are structured around an institution - America, the justice system, the castle - as the characters they are composed of operate either as cogs of this institution or demonstrate some function outside of this institution, usually offering some kind of help to the protagonist. However, despite these cogs, the institution never serves its purpose in the same way that, despite these helpers, the protagonist is never helped, precisely because of a schism between the realms of justice and charity.